2002
DOI: 10.1002/1616-3028(20020201)12:2<149::aid-adfm149>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Elastomer Hydrogels via Self-Assembly of an Elastin-Mimetic Triblock Polypeptide

Abstract: Protein‐based analogues of conventional thermoplastic elastomers can be designed with enhanced properties as a consequence of the precise control of primary structure. Protein 1 undergoes a reversible sol–gel transition, which results in the formation of a well‐defined elastomeric network above a lower critical solution temperature. The morphology of the network is consistent with selective microscopic phase separation of the endblock domains. This genetic engineering approach provides a method for specificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(181 citation statements)
references
References 31 publications
7
170
1
1
Order By: Relevance
“…They also used different solvent environments, such as mixtures of trifluoroethanol (TFE) and water, to change the secondary structure of the proteins. When the protein solution was electrospun to form nanofiber scaffolds, using solvent mixtures resulted in varied microstructures and mechanical properties [70,201,202]. As florinated alcohols are known to form strong solid-state complexes with polyamides, TFE is a good solvent for all three blocks of the copolymer.…”
Section: Elastin-mimetic Polypeptidescontrasting
confidence: 38%
See 2 more Smart Citations
“…They also used different solvent environments, such as mixtures of trifluoroethanol (TFE) and water, to change the secondary structure of the proteins. When the protein solution was electrospun to form nanofiber scaffolds, using solvent mixtures resulted in varied microstructures and mechanical properties [70,201,202]. As florinated alcohols are known to form strong solid-state complexes with polyamides, TFE is a good solvent for all three blocks of the copolymer.…”
Section: Elastin-mimetic Polypeptidescontrasting
confidence: 38%
“…Rheological measurements of an aqueous triblock copolymer solution as a function of temperature showed that the copolymers would be well-suited for biomedical applications. The loss modulus (G″) is higher than the storage modulus (G′) below the LCST, and G′ is higher than G″ above the LCST, indicating that above the LCST the solution converts from liquid-like to solid-like viscoelastic behavior [70,153,201,202]. They found that changing the length or hydrophilicity of the middle largely affected the viscoelastic and mechanical behavior of the copolymers when the same plastic domain was used [202].…”
Section: Elastin-mimetic Polypeptidessupporting
confidence: 38%
See 1 more Smart Citation
“…Temperature-dependent formation of micelles was verified by dynamic light scattering (DLS), and differential scanning calorimetry (DSC) was used to measure the enthalpy of self-assembly. Subsequently, a tri-block copolymer was prepared using the same hydrophilic block capped on both ends by hydrophobic blocks using VPAVG-(IPAVG) 4 , and conventional TEM images showed the formation of spherical and cylindrical worm-like micelles [35]. Interestingly 1 H-13 C heteronuclear correlation multiple quantum coherence NMR spectroscopy demonstrated that hydrophobic block residues (isoleucine and alanine) become motionally restricted above the T t , while the hydrophilic block residues do not, suggesting temperature-dependent formation of hydrophobic nanodomains [35].…”
Section: Block Co-polymersmentioning
confidence: 44%
“…For example, elastin is an extracellular matrix protein that provides elasticity to connective tissue (Muiznieks et al 2010). It readily self-assembles, and synthetic hydrogels made from recombinant elastin proteins undergo a temperaturesensitive phase change that makes them useful for drug delivery (Wright et al 2002). Spider silk, on the other hand, is an extraordinarily tough material (Lazaris 2002); spider silk proteins expressed in Escherichia coli and extruded through an artificial spinneret have mechanical properties similar to the natural fiber (Xia et al 2010).…”
Section: Frontier Two: Synthetic Biomaterials and Programmable Mattersupporting
confidence: 40%